Testing for Persistence in German Green and Brown Stock Market Indices - Guglielmo Maria Caporale; Luis Alberiko Gil-Alana; Sakiru A. Solarin; OlaOluwa S. Yaya (CESifo GmbH, 2024)
This study examines the stochastic properties of German green and brown stock prices; more specifically, fractional integration methods are applied to daily data on representative green and brown stock indices for the Berlin, Dusseldorf, Frankfurt, Gettex, Munich, and Stuttgart stock exchanges over the period from 13 May 2019 to 8 May 2024. The results indicate a higher degree of persistence in the case of green stock prices vis-à-vis brown ones, although the differences are not statistically significant over the full sample. However, when splitting the sample into three subperiods (pre-Covid-19, Covid-19 and post-Covid-19), statistically significant differences are found, especially during the pandemic period. Moreover, the estimation of a GARCH (1,1) model for stock returns shows that their conditional volatility is characterised by lower persistence and shorter half-lives in the case of brown stocks.
Keywords: C22; G10; Q50; 330; green stocks; brown stocks; fractional integration persistence; Covid-19 pandemic; Germany